2018
DOI: 10.1021/acs.est.8b01071
|View full text |Cite
|
Sign up to set email alerts
|

Does Size Matter? An Experimental Evaluation of the Relative Abundance and Decay Rates of Aquatic Environmental DNA

Abstract: Environmental DNA (eDNA) is increasingly used to monitor aquatic macrofauna. Typically, short mitochondrial DNA fragments are targeted because these should be relatively more abundant in the environment as longer fragments will break into smaller fragments over time. However, longer fragments may permit more flexible primer design and increase taxonomic resolution for eDNA metabarcoding analyses, and recent studies have shown that long mitochondrial eDNA fragments can be extracted from environmental water samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
165
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(170 citation statements)
references
References 59 publications
5
165
0
Order By: Relevance
“…It is also the first to show the water temperature‐dependent degradation of marine fish eDNA. As moderately higher temperatures (<50°C) stimulate microbial metabolism and exonuclease activity (Corinaldesi, Beolchini, & Dell'Anno, ; Poté, Ackermann, & Wildi, ), and high fish density can lead to the increase in microbial activity (Barnes et al, ; Bylemans et al, ), these results are likely to support the hypothesis that the activity and abundance of microbes and extracellular nucleases significantly affect eDNA degradation (Barnes & Turner, ; Levy‐Booth et al, ; Nielsen, Johnsen, Bensasson, & Daffonchio, ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It is also the first to show the water temperature‐dependent degradation of marine fish eDNA. As moderately higher temperatures (<50°C) stimulate microbial metabolism and exonuclease activity (Corinaldesi, Beolchini, & Dell'Anno, ; Poté, Ackermann, & Wildi, ), and high fish density can lead to the increase in microbial activity (Barnes et al, ; Bylemans et al, ), these results are likely to support the hypothesis that the activity and abundance of microbes and extracellular nucleases significantly affect eDNA degradation (Barnes & Turner, ; Levy‐Booth et al, ; Nielsen, Johnsen, Bensasson, & Daffonchio, ).…”
Section: Discussionmentioning
confidence: 76%
“…The main factors associated with eDNA shedding are (1) the number and the biomass of organisms (Klymus, Richter, Chapman, & Paukert, 2015;Takahara, Minamoto, Yamanaka, Doi, & Kawabata, 2012); (2) the developmental stage of the organisms (Maruyama, Nakamura, Yamanaka, Kondoh, & Minamoto, 2014); (3) the behavior of organisms (Dunn, Priestley, Herraiz, Arnold, & Savolainen, 2017); and (4) the stress against organisms (Bylemans, Furlan, Gleeson, Hardy, & Duncan, 2018;Pilliod et al, 2014). In addition, considering that feed intake increased the eDNA shedding (Klymus et al, 2015), eDNA shedding rate is likely to depend on (5) the metabolism and physiological activity of the organisms.…”
mentioning
confidence: 99%
“…Otherwise, the shorter barcoding region amplified by the Teleo primers could also increase the detection of fish taxa due to an increased ability to recover highly degraded eDNA. Although recent studies have suggested that the aquatic environment may preserve eDNA relatively well (Bylemans et al., ; Piggott, ), more research is needed to evaluate the effect of barcode length on eDNA metabarcoding surveys. Overall, the results show that even within an ecoregion the performance of eDNA metabarcoding primers may differ depending on the local biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…First, a positive relationship exists between the length of the internally amplified barcode and its taxonomic resolution power (Coissac et al., ; Meusnier et al., ) but the ability to recover DNA from environmental samples can be negatively impacted by the size of the DNA fragments (Deagle, Eveson, & Jarman, ; Jo et al., ). However, a number of recent studies have shown that this may be less problematic for eDNA derived from water samples (Bylemans, Furlan, Gleeson, Hardy, & Duncan, ; Deiner et al., ; Piggott, ). Second, reducing primer‐template mismatches can minimize biases arising from the PCR amplification but may inadvertently decrease the specificity of the primers to the taxonomic group of interest as these primers are more likely to bind to highly conserved regions (Pinol, Mir, Gomez‐Polo, & Agusti, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of species-specific eDNA assays, the design and validation of the assay represents a critical first 47 step (Geerts et al, 2018). During assay design, it is fundamental to ensure a high target specificity 48 (Bylemans et al, 2018) by selecting suitable amplicon lengths, in-silico simulations and testing against 49 amplification of non-target DNA. In-vitro laboratory validation should then ascertain that the assay 50 complies with established guidelines (Bustin et al, 2009) and that limits of detection (LOD) and 51 quantification (LOQ) are established.…”
Section: Introduction 37mentioning
confidence: 99%